2017
DOI: 10.4236/ajps.2017.84059
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Mapping Forest Floor Distributions of Common Bryophytes Using a LiDAR-Derived Depth-to-Water Index

Abstract: This article describes how the cartographic depth-to-water (DTW) index in combination with other variables can be used to quantify, model and map the distribution of common forest floor bryophytes, at 1 m resolution. This was done by way of a case study, using 12 terrain and climate representative locations across New Brunswick, Canada. The presence/absence by moss species was determined at each location along upland-to-wetland transects within >10-m spaced 1-m 2 forest floor plots. It was found that Bazzania … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The urbanization gradient studied here was clearly associated with smaller red mottles, higher drainage and decreasing cover of bryophytes, a species group highly sensitive to changes in light and hydrological regime (Ehrenfeld and Schneider, 1991; Nelson and Halpern, 2005; Goguen and Arp, 2017). Given that the studied swamps had a closed canopy (89% of shade on average), the observed decrease of bryophytes points to altered hydrological regimes as a major environmental change induced by urbanization.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The urbanization gradient studied here was clearly associated with smaller red mottles, higher drainage and decreasing cover of bryophytes, a species group highly sensitive to changes in light and hydrological regime (Ehrenfeld and Schneider, 1991; Nelson and Halpern, 2005; Goguen and Arp, 2017). Given that the studied swamps had a closed canopy (89% of shade on average), the observed decrease of bryophytes points to altered hydrological regimes as a major environmental change induced by urbanization.…”
Section: Discussionmentioning
confidence: 89%
“…The cover of bryophytes (largely dominated by Sphagnum spp. ), vernal pools and bare ground surfaces was additionally estimated using the same classes as for plant cover to approximate hydric conditions at soil surface (Goguen and Arp, 2017).…”
Section: Environmental Variablesmentioning
confidence: 99%
“…The DTW index has been used in previous studies to map and model the distribution of common forest floor bryophyte species with a high degree of accuracy (Goguen & Arp, ). We also previously demonstrated that bryophyte cover, richness and composition in unharvested forests were related to site moisture, as indicated by the DTW index, but that these relationships varied by forest type (Bartels, Caners, Ogilvie, White, & Macdonald, ).…”
Section: Introductionmentioning
confidence: 99%